2014
DOI: 10.1002/jcla.21708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Plasma miR‐21 in New‐Onset Systemic Lupus Erythematosus Patients

Abstract: Plasma miR-21 in SLE patients from Central China is overexpressed. Since circulating miR-21 is aberrantly expressed in many diseases, the applying of it as a disease biomarker should be considered carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Further experiments revealed that miR‐21 indirectly downregulated DNMT1 expression by targeting an important autoimmune gene, RASGRP1 . Plasma miR‐21 level in patients with SLE was higher than that of healthy controls and significantly correlated with the level of plasma complement C3, C4 and serum uric acid in patients with SLE .…”
Section: Mirnas In Autoimmune Diseases With Skin Involvementmentioning
confidence: 96%
“…Further experiments revealed that miR‐21 indirectly downregulated DNMT1 expression by targeting an important autoimmune gene, RASGRP1 . Plasma miR‐21 level in patients with SLE was higher than that of healthy controls and significantly correlated with the level of plasma complement C3, C4 and serum uric acid in patients with SLE .…”
Section: Mirnas In Autoimmune Diseases With Skin Involvementmentioning
confidence: 96%
“…moreover, mirs are not located only intracelullarly, but their presence in tissues and body fluids, such as the plasma and the serum [17][18][19][20][21][22][23] , makes them potential blood-based biomarkers of disease development and activity as well as for predicting therapeutic responses. in sle, different patterns of mirs expression have been detected in the plasma [18][19][20][21] , serum 22,23 and urine 22,23 as well as in peripheral mononuclear cells (pBmcs) (ref. [24][25][26][27][28] ).…”
Section: Micrornas and Slementioning
confidence: 99%
“…MiR-21 is detected in higher concentration in plasma from newly diagnosed, treatment-naive lupus patients relative to healthy individuals [6], suggesting that elevated urinary miR-21 may predict a high risk of renal function loss [29]. In lupus mice, miR-21 expression decreases after treatment with hydroxychloroquine, an immunomodulator commonly used for treatment of various SLE manifestations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-21 is detected in higher concentration in plasma from newly diagnosed, treatment-naive lupus patients compared to healthy individuals [6, 7] and increased concentration of urinary miR-21 may predict a high risk of renal function loss [8]. In lupus prone mice, miR-21 expression in T cells, pDCS, PBMCs and urine is reduced after treatment with hydroxychloroquine [9].…”
Section: Introductionmentioning
confidence: 99%